The structure, stratigraphy and hydrocarbon potential of the onshore early Cretaceous Basin, West-Gippsland, Victoria, Australia - Aghaei, Hamed (2017)
The Gippsland Basin, one of the largest Australian oil and gas basins, is located in southeast Australia where it lies across the Palaeozoic Tasman Fold Belt. It developed during Early and Late Cretaceous, north-south lithospheric extension between Australia and Antarctica, and the Late Cretaceous separation of Australia from the Lord Howe Rise/Campbell Plateau. The Strzelecki Group, the oldest unit in the Gippsland Basin, was deposited between ~150 Ma (Tithonian) and ~100 Ma (Albian), as a result of Early Cretaceous extension associated with the development of the rift basin bounded by the Foster and Lake Wellington faults. It mainly consists of interbedded mudstones, sandstones and coal beds. This group plays the role of basement in eastern part of the basin, however, it experienced uplift to the west that provides spectacular outcrops especially along the coastal area between San Remo and Inverloch. There are still questions regarding structure, stratigraphy and hydrocarbon potential of this group in the Gippsland region. The present day thickness of this group in the west Gippsland area and the amount of erosion during Late Cretaceous uplift is still controversial, the structural framework is not well known and the hydrocarbon potential was not well evaluated in the past. The present study mainly focused on unique coastal outcrops of Strzelecki Group in the Wonthaggi area of west Gippsland to interpret their structure, stratigraphy and hydrocarbon source potential via extensive field work including mapping, logging, sampling, and also interpreting the results of optical and instrumental analyses on thermal maturity, spore-pollen zone and source potential. It has been revealed that the outcrops are non-marine, interbedded mudstone and fine-medium grained sandstone with numerous coal beds. Three generations of faults have been mapped, which, in chronological order from oldest to youngest, have dominant trends of E-W, NW-SE and NE-SW. The section is intruded by a number of dominantly NW trending dykes which ...